The moral foundations of restraint: Partisanship, military training, and norms of civilian protection. (September 2022) - Bell, Andrew M; Gift, Thomas; Monten, Jonathan
How does partisan identification shape the attitudes of US military officers toward the protection of civilians in war? Drawing on unique cross-cohort surveys of soon-to-be commissioned officers in 12 Army Reserve Officers' Training Corps (ROTC) training battalions, we find that Democratic-leaning cadets generally prioritize norms of civilian protection more than Republican-leaning cadets when confronted with competing values of military advantage and force protection as part of a 'combatant's trilemma'. This gap remains partially resilient after sustained exposure to military training and socialization, including in the norms of restraint embodied by principles of combat ethics and the law of war. We attribute these partisan differences to insights from Moral Foundations Theory (MFT), which suggests that the moral values of Democrats and Republicans guide their views toward the individual use of force in combat. Our findings have important implications for comprehending the impact of political ideology and military training and socialization on attitudes regarding restraint toward civilians in war. Given the widely recognized conservative composition of the US military's membership, these findings may help to further inform understanding of US military operations and the underlying causes of US adherence to – or violation of – the laws of armed conflict.